2019
DOI: 10.5713/ajas.18.0630
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and health of nursing lambs supplemented with inulin and Lactobacillus casei

Abstract: Objective This experiment was designed to evaluate the effects of Agave tequilana inulin and Lactobacillus casei ( L. casei ) on growth performace, hematological variables, serum metabolites, and total coliforms in nursing lambs. Methods The experimental design was completely randomized; treatments were T1, control (pre-starter concentrate, PC), T2: T1+2% inulin, and T3: T1+2% inulin+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
4
11
0
5
Order By: Relevance
“…This may be due to the increased digestibility of the NDF and the DM in their experiment, and also, may be correlated with rumen development ( Lesmeister et al, 2004 ). However, without the effect of experimental treatments on feed intake, ADG was improved on d 0 to d 21 and d 0 to d 63, which consistent with the previous results ( Ayala-Monter et al, 2019 ). They reported that improvement in ADG without altering feed intake was due to improved FE and nutrient digestibility.…”
Section: Discussionsupporting
confidence: 91%
“…This may be due to the increased digestibility of the NDF and the DM in their experiment, and also, may be correlated with rumen development ( Lesmeister et al, 2004 ). However, without the effect of experimental treatments on feed intake, ADG was improved on d 0 to d 21 and d 0 to d 63, which consistent with the previous results ( Ayala-Monter et al, 2019 ). They reported that improvement in ADG without altering feed intake was due to improved FE and nutrient digestibility.…”
Section: Discussionsupporting
confidence: 91%
“…The higher blood concentration of cholesterol during the second period may be explained by a differential tissue requirement during growth [ 36 , 37 ], although this varies among the different breeds [ 38 ]. This is important when considering dietary supplementation with choline and other nutrients that affect lipid metabolism at different developmental stages [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…On day 55 of the experimental phase, blood samples were taken from the jugular vein of the lambs, before the morning feeding (08:00 h) with the purpose of determining hematological and biochemical parameters. For determining the hematological parameters, the methodology described by Ayala et al was followed [ 28 ]. For this, 5 mL of blood was extracted from each lamb in tubes BD Vacutainer ® K2 EDTA with anticoagulant.…”
Section: Methodsmentioning
confidence: 99%